In the adjoining figure,


In the adjoining figure, if AB = BC and BX = BY, then show that AX = CY


We have, AB = BC …(i)

and BX = BY ,.,.(ii)

According to Euclid’s axiom, if equals are subtracted from equals, the remainders are equal. So, on subtracting Eq. (ii) from Eq. (i), we get

AB- BX = BC – BY

=> AX = CY [from figure]

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now